Pengembangan media audio visual sebagai media pembelajaran: Kesehatan reproduksi bagi remaja tunagrahita - Apri Nur Wulandari; Barkah Wulandari (MEDIA ILMU KESEHATAN, 2021)
Background: Teachers have experience difficulties in delivering reproductive health material to adolescent with intellectual disability. Until now, learning reproductive health has not been taught in a structured manner in learning in schools because it has not been included in the educational curriculum structure in special schools. The lack of references or guidelines for parents and teachers shows the importance of media learning.Objective: This study aims to develop audio-visual media as a learning media for reproductive health for adolescent with intellectual disability. Methods: This research is a Research and Development (R&D). The first step is a need assessment of the problems and experiences of the parents, the teacher then continues to draft the instructional media in audio-visual form. The validity test was carried out by media and material experts as well as field testing on teachers at SLB N 2 Yogyakarta.Results: The feasibility of reproductive health audio-visual media for adolescents with intellectual disability based on material experts is 74 points (feasible with a good predicate), the eligibility of media experts is 90 points (feasible with very good predicate), and the eligibility of teachers is 81.5 points (feasible with very good).Conclusion: The design of the audio-visual media that has been made feasible to be tested on adolescents with intellectual disability after passing the revision stage.